A search for binary star companions to the KELT planet hosts and a comparison sample. i. results of DSSI observations - Coker, Carl T.; Gaudi, B. Scott; Pogge, Richard W.; Horch, Elliott (The Astronomical Journal, 2017)
We are conducting a search for binary companions around 11 hot-Jupiter hosts from the Kilodegree Extremely Little Telescope (KELT) survey and a large comparison sample of stars shown by KELT to not host a transiting hot Jupiter. The primary stars are bright (7.5 < V < 11) and of similar distance from Earth (100 < d < 300 pc). In this paper, we present the results of our observations using the Differential Speckle Survey Instrument. We observed 9 of the 14 KELT planet hosts that are visible from the northern hemisphere and 51 comparison stars, discovering two new potential companions and re-observing two previously known possible binary systems and one confirmed binary system. We provide an estimate of the chance alignment probability for our observed candidate binaries. © 2017 The American Astronomical Society. All rights reserved.
3 citations (Crossref) [2023-10-31]
Keywords: Astrometry; binaries: close; binaries: general; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: formation

Exclusion of stellar companions to exoplanet host stars - Wittrock, Justin M.; Kane, Stephen R.; Horch, Elliott P.; Howell, Steve B.; Ciardi, David R.; Everett, Mark E. (The Astronomical Journal, 2017)
Given the frequency of stellar multiplicity in the solar neighborhood, it is important to study the impacts this can have on exoplanet properties and orbital dynamics. There have been numerous imaging survey projects established to detect possible low-mass stellar companions to exoplanet host stars. Here, we provide the results from a systematic speckle imaging survey of known exoplanet host stars. In total, 71 stars were observed at 692 and 880 nm bands using the Differential Speckle Survey Instrument at the Gemini-north Observatory. Our results show that all but two of the stars included in this sample have no evidence of stellar companions with luminosities down to the detection and projected separation limits of our instrumentation. The mass-luminosity relationship is used to estimate the maximum mass a stellar companion can have without being detected. These results are used to discuss the potential for further radial velocity follow-up and interpretation of companion signals. © 2017. The American Astronomical Society. All rights reserved..
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-303-042-496-092, pop00140 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

Assessing the effect of stellar companions from high-resolution imaging of Kepler objects of interest - Hirsch, Lea A.; Ciardi, David R.; Howard, Andrew W.; Everett, Mark E.; Furlan, Elise; Saylors, Mindy; Horch, Elliott P.; Howell, Steve B.; Teske, Johanna; Marcy, Geoffrey W. (The Astronomical Journal, 2017)
We report on 176 close (<2″) stellar companions detected with high-resolution imaging near 170 hosts of Kepler Objects of Interest (KOIs). These Kepler targets were prioritized for imaging follow-up based on the presence of small planets, so most of the KOIs in these systems (176 out of 204) have nominal radii <6 . Each KOI in our sample was observed in at least two filters with adaptive optics, speckle imaging, lucky imaging, or the Hubble Space Telescope. Multi-filter photometry provides color information on the companions, allowing us to constrain their stellar properties and assess the probability that the companions are physically bound. We find that 60%-80% of companions within 1″ are bound, and the bound fraction is >90% for companions within 0.″5; the bound fraction decreases with increasing angular separation. This picture is consistent with simulations of the binary and background stellar populations in the Kepler field. We also reassess the planet radii in these systems, converting the observed differential magnitudes to a contamination in the Kepler bandpass and calculating the planet radius correction factor, X R = R p(true)/R p(single). Under the assumption that planets in bound binaries are equally likely to orbit the primary or secondary, we find a mean radius correction factor for planets in stellar multiples of X R = 1.65. If stellar multiplicity in the Kepler field is similar to the solar neighborhood, then nearly half of all Kepler planets may have radii underestimated by an average of 65%, unless vetted using high-resolution imaging or spectroscopy. © 2017. The American Astronomical Society. All rights reserved.
49 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-135-164-854-429, pop00043 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: fundamental parameters; techniques: high angular resolution; techniques: photometric

Observations of binary stars with the Differential Speckle Survey Instrument. VII. Measures from 2010 September to 2012 February at the WIYN Telescope - Horch, Elliott P.; Casetti-Dinescu, Dana I.; Camarata, Matthew A.; Bidarian, Akbar; Altena, William F. van; Sherry, William H.; Everett, Mark E.; Howell, Steve B.; Ciardi, David R.; Henry, Todd J.; Nusdeo, Daniel A.; Winters, Jennifer G. (The Astronomical Journal, 2017)
We report on speckle observations of binary stars carried out at the WIYN Telescope over the period from 2010 September through 2012 February, providing relative astrometry for 2521 observations of 883 objects, 856 of which are double stars and 27 of which are triples. The separations measured span a range of 0.01-1.75 arcsec. Wavelengths of 562, 692, and 880 nm were used, and differential photometry at one or more of these wavelengths is presented in most cases. 66 components were resolved for the first time. We also estimate detection limits at 0.2 and 1.0 arcsec for high-quality observations in cases where no companion was seen, a total of 176 additional objects. Detection limits vary based on observing conditions and signal-to-noise ratio, but are approximately 4 mag at 0.2 arcsec and 6 mag at 1.0 arcsec on average. Analyzing the measurement precision of the data set, we find that the individual separations obtained have linear measurement uncertainties of approximately 2 mas, and photometry is uncertain to approximately 0.1 mag in general. This work provides fundamental, well-calibrated data for future orbit and mass determinations, and we present three first orbits and total mass estimates of nearby K-dwarf systems as examples of this potential. © 2017. The American Astronomical Society. All rights reserved..
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-417-913-195-546, pop00017 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Four sub-Saturns with dissimilar densities: Windows into planetary cores and envelopes - Petigura, Erik A.; Sinukoff, Evan; Lopez, Eric D.; Crossfield, Ian J. M.; Howard, Andrew W.; Brewer, John M.; Fulton, Benjamin J.; Isaacson, Howard T.; Ciardi, David R.; Howell, Steve B.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
We present results from a Keck/HIRES radial velocity campaign to study four sub-Saturn-sized planets, K2-27b, K2-32b, K2-39b, and K2-108b, with the goal of understanding their masses, orbits, and heavy-element enrichment. The planets have similar sizes (RP=4.5-5.5 ), but have dissimilar masses (MP=16-60 ), implying a diversity in their core and envelope masses. K2-32b is the least massive (MP = 16.5 ± 2.7 M) and orbits in close proximity to two sub-Neptunes near a 3:2:1 period commensurability. K2-27b and K2-39b are significantly more massive at MP = 30.9 ± 4.6 M and MP = 39.8 ± 4.4 M, respectively, and show no signs of additional planets. K2-108b is the most massive at MP = 59.4 ± 4.4 M, implying a large reservoir of heavy elements of about ≈50 . Sub-Saturns as a population have a large diversity in planet mass at a given size. They exhibit remarkably little correlation between mass and size; sub-Saturns range from ≈6-60 M, regardless of size. We find a strong correlation between planet mass and host star metallicity, suggesting that metal-rich disks form more massive planet cores. The most massive sub-Saturns tend to lack detected companions and have moderately eccentric orbits, perhaps as a result of a previous epoch of dynamical instability. Finally, we observe only a weak correlation between the planet envelope fraction and present-day equilibrium temperature, suggesting that photo-evaporation does not play a dominant role in determining the amount of gas sub-Saturns accrete from their protoplanetary disks. © 2017. The American Astronomical Society. All rights reserved..
62 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-273-244-483-27X, pop00045 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: composition; planets and satellites: detection; planets and satellites: dynamical evolution and stability; planets and satellites: formation; planets and satellites: gaseous planets; planets and satellites: interiors

Characterizing K2 candidate planetary systems orbiting Low-mass stars. II. Planetary Systems observed during campaigns 1–7 - Dressing, Courtney D.; Vanderburg, Andrew; Schlieder, Joshua E.; Crossfield, Ian J. M.; Knutson, Heather A.; Newton, Elisabeth R.; Ciardi, David R.; Fulton, Benjamin J.; Gonzales, Erica J.; Howard, Andrew W.; Isaacson, Howard; Livingston, John; et al. (The Astronomical Journal, 2017)
We recently used near-infrared spectroscopy to improve the characterization of 76 low-mass stars around which K2 had detected 79 candidate transiting planets. 29 of these worlds were new discoveries that had not previously been published. We calculate the false positive probabilities that the transit-like signals are actually caused by non-planetary astrophysical phenomena and reject five new transit-like events and three previously reported events as false positives. We also statistically validate 17 planets (7 of which were previously unpublished), confirm the earlier validation of 22 planets, and announce 17 newly discovered planet candidates. Revising the properties of the associated planet candidates based on the updated host star characteristics and refitting the transit photometry, we find that our sample contains 21 planets or planet candidates with radii smaller than 1.25 R ⊕, 18 super-Earths (1.25-2 R ⊕), 21 small Neptunes (2-4 R ⊕), three large Neptunes (4-6 R ⊕), and eight giant planets (>6 R ⊕). Most of these planets are highly irradiated, but EPIC 206209135.04 (K2-72e, ), EPIC 211988320.01 (), and EPIC 212690867.01 () orbit within optimistic habitable zone boundaries set by the "recent Venus" inner limit and the "early Mars" outer limit. In total, our planet sample includes eight moderately irradiated 1.5-3 R ⊕ planet candidates (F p ≲ 20 F ⊕) orbiting brighter stars (Ks < 11) that are well-suited for atmospheric investigations with the Hubble, Spitzer, and/or James Webb Space Telescopes. Five validated planets orbit relatively bright stars (Kp < 12.5) and are expected to yield radial velocity semi-amplitudes of at least 2 m s-1. Accordingly, they are possible targets for radial velocity mass measurement with current facilities or the upcoming generation of red optical and near-infrared high-precision RV spectrographs. © 2017. The American Astronomical Society. All rights reserved..
68 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: fundamental parameters; stars: fundamental parameters; stars: late-type; stars: low-mass; techniques: spectroscopic

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-258-082-978-883, pop00029 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric